Extraction of Bioactive Compounds (Mangiferin) from Mahkota Dewa (Phaleria macrocarpa) Fruits Using Subcritical Water: Effect of Process Parameters on Extraction Yield - Nurmaryam Aini, Hashim; Ummi Najihah, Md. Hashim; Siti Kholijah, Abdul Mudalip; Noorlisa, Harun; Fatmawati, Adam; Rohaida, Che Man; Siti Zubaidah, Sulaiman; Zatul Iffah, Mohd Arshad; Shalyda, Md Shaarani (Universiti Kebangsaan Malaysia, 2017)
Mahkota Dewa (Phaleria macrocarpa) is a popular herbal plant that is indigenous to Indonesia and Malaysia. The bioactive ingredients in the plant contain antihistamine, antioxidant, and anti-cancer compound. In this work, experimental study was performed using subcritical water extraction (SWE) method to extract bioactive compound namely mangiferin from Mahkota Dewa fruits. A sequential screening strategy using one-factor-at-a-time (OFAT) was carried out at different solid to solvent ratios (30 – 70 g/L), temperatures (50 – 150 °C) and extraction times (3 – 7 hours). The yield of mangiferin extracted was measured using high performance liquid chromatography (HPLC). The results show that the solid to solvent ratio, extraction temperature and time cause significant effect on the mangiferin yield. The best operating conditions for extracting Mahkota Dewa fruit with subcritical method is 60 g/L solid to solvent ratio and 100°C extraction temperature for 5 hours with mangiferin yield of 3.202% w/w.